Influence of temperature and chemical composition on water sorption isotherms for dry-cured ham. (April 2020) - Leonardo Betiol, Lilian Fachin; Evangelista, Rodrigo Rodrigues; Ribeiro Sanches, Marcio Augusto; Basso, Rodrigo Corrêa; Gullón, Beatriz; Lorenzo, Jose M.; Carla da Silva Barretto, Andrea; Romero, Javier Telis
Abstract: In this research, the sorption isotherms of seven brands of commercial dry-cured ham with different chemical composition were assessed simulating the conditions of storage at three temperatures. For this purpose, the dry-cured hams were chemically analyzed and their sorption isotherms were determined at 7, 17 and 27 °C through the static gravimetric method. The sorption isotherms corresponded to the characteristics of BET III type isotherm due to the high protein content and soluble compounds as salts present in the samples. The experimental data were fitted using GAB, Peleg, Oswin and Henderson models, being the GAB model the one which best described the isotherms of sorption since it presented the best adjustment (RAdj 2 ≥ 0.999 and RMSE ≤ 0.023). The equilibrium moisture content of the dry-cured ham decreased with increasing temperature. The different chemical composition of the samples, mostly in terms of the sodium chloride content affected the moisture sorption isotherms. The results indicated that at a given water activity, equilibrium moisture content increased when the NaCl content increased at all temperatures evaluated. Highlights: The sorption isotherms obtained correspond to the characteristics of BET III type isotherm. GAB model was the more suitable describing experimental sorption data at different temperatures of storage. The sorption capacity of dry-cured ham samples was temperature-dependent. NaCl content also affected significantly to the sorption isotherms.